IMPLEMENTATION OF THE TGT COOPERATIVE LEARNING MODEL WITH THE ASSISTANCE OF ANIMATION VIDEO MEDIA TO IMPROVE STUDENTS' LEARNING OUTCOMES OF CLASS VIIIE SMPN1 WAINGAPU - Trifonia May Nggadi; Yohana Makaborang; Yohana Ndjoeroemana (Jurnal Eduscience, 2023)
The low student learning outcomes of SMPN 1 Waingapu motivated this research. This study aims to demonstrate how the application of the TGT cooperative learning paradigm in class VIII E of SMPN 1 Waingapu is combined with animated video content to improve student learning outcomes. This research is a classroom action research (CAR) involving 28 students in pre-cycle, cycle I, and cycle II activities. Utilizing quantitative descriptive in data analysis. While the emotive domain uses an evaluation rubric, the cognitive domain uses a pretest and posttest. Based on the findings of this study, students' science learning outcomes at SMPN 1 Waingapu can be improved with the TGT learning model with the help of animated video media. The number of students who completed 2 with a percentage of 7% obtained an average of 63 overall student learning outcomes during the pre-cycle. The cognitive component was then completed by 15 students in cycle I with a percentage of 54%, and by 13 students with a percentage of 47%. The emotional component of the first cycle has an average value of 36.5 and the average percentage is 66.7%. The results of the second cycle of student learning show. The average value of the emotional component of the second cycle is 75.5 with a high percentage of 100.0%. Thus it can be stated that the use of the TGT cooperative learning paradigm in class VIIIE of SMPN 1 Waingapu with the use of animated video media can improve student learning outcomes.